The Standardized World Income Inequality Database - Solt, Frederick (Social science quarterly, 2016)
Objective. Since 2008, the Standardized World Income Inequality Database (SWIID) has provided income inequality data that seek to maximize comparability while providing the broadest possible coverage of countries and years. This article describes the current SWIID’s construction, highlighting differences from its original version, and reevaluates the SWIID’s utility to cross-national income inequality research in light of recently available alternatives. Methods. Coverage of inequality data sets is assessed across country-years; comparability is evaluated in terms of success in predicting the Luxembourg Income Study (LIS), recognized in the field as the gold standard in comparability, before those data are released. Results. The SWIID offers coverage double that of the next largest income inequality data set, and its record of comparability is three to eight times better than those of alternate data sets. Conclusions. As its coverage and comparability far exceed those of the alternatives, the SWIID remains better suited for broadly cross-national research on income inequality than other available sources.